2008
DOI: 10.1007/s11746-008-1260-8
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Soyamide Ferulate

Abstract: Ferulic acid (4-hydroxy-3-methoxycinnamic acid) is a phytochemical antioxidant that is widely distributed throughout the plant kingdom. Cinnamic acid derivatives are used as biobased ultraviolet (UV) absorbers in sunscreen formulations. Soybean oil ferulate, a biobased UV absorber, was synthesized by reacting soyamide with ferulic acid. The resulting product was characterized by infrared (IR) and nuclear magnetic resonance (NMR) spectroscopy, and gel permeation chromatography (GPC). Spectroscopic studies measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…CDFAs spectra show new bands at 3346, 1624 and 1046 cm -1 attributed to N-H stretching, C=O stretching and C-N stretching of amide, respectively. The disappearance of peaks at 1743 and 1162 cm -1 and appearance of peaks at 3346, 1624 and 1046 cm -1 indicate that fatty amides have been formed 10) . EFEs spectra show the presence of the major absorption bands of palm oil but with no existence of peaks which correspond to amide.…”
Section: Ftir Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…CDFAs spectra show new bands at 3346, 1624 and 1046 cm -1 attributed to N-H stretching, C=O stretching and C-N stretching of amide, respectively. The disappearance of peaks at 1743 and 1162 cm -1 and appearance of peaks at 3346, 1624 and 1046 cm -1 indicate that fatty amides have been formed 10) . EFEs spectra show the presence of the major absorption bands of palm oil but with no existence of peaks which correspond to amide.…”
Section: Ftir Spectramentioning
confidence: 99%
“…Vegetable oils are given considerable attention as they are biodegradable, renewable, non toxic, environmental friendly and easily available. Triglycerides in oils can be converted into their fatty amides via amidation 9,10) . Neeraj et al (2007) reported that fatty amides were synthesized from fatty acids with urea instead of amine compounds 11) .…”
Section: Introductionmentioning
confidence: 99%
“…Characteristic bands of corn oil were observed at 3011, 2923, 2856, 1742, 1464, 1162, and 723 cm -1 resulting from C-H stretching of CH=CH, C-H asymmetric stretching of CH 2 , C-H symmetric stretching of CH 2 , C=O stretching of ester (glyceride), CH 2 scissoring, O-C-C stretching, and CH 2 rocking, respectively 11) CDFAs spectra show new bands at 3342, 1623 and 1045 cm -1 attributed to N-H stretching, C=O stretching and C-N stretching of amide, respectively. The disappearance of peaks at 1742 and 1162 cm -1 and appearance of peaks at 3342, 1623 and 1045 cm -1 indicate that fatty acyl urea have been formed 10) .…”
Section: Ftir Spectramentioning
confidence: 99%
“…Vegetable oils are given considerable attention as they are biodegradable, renewable, non toxic, environmental friendly and easily available. Triglycerides in oils can be converted into their fatty amides via amidation 10,11) . Fatty amides were synthesized from fatty acids with urea instead of amine compounds 12) .…”
Section: Introductionmentioning
confidence: 99%
“…15,16 The triglyceride ester moieties are amenable to modification via transesterification, amidation, and alcoholysis. [17][18][19][20] Conversion of vegetable oils to vegetable oil macromonomers (VOMMs) yields bio-based comonomers for synthesizing autooxidizable latexes. 21 Castor oil and lesquerella oil contain 89% ricinoleic acid and 69% lesquerolic acid, respectively, both of which possess a secondary hydroxyl group that offers an additional avenue for modification.…”
Section: Introductionmentioning
confidence: 99%